Neuroimaging Predictors of Clinical Outcome in Acute Basilar Artery Occlusion - Garg, Ravi; Biller, José (Frontiers in Neurology, 2017)
Certain early neuroimaging findings are independent predictors of clinical outcome in acute basilar artery occlusion. These imaging findings may serve as important baseline imaging characteristics as well as subgroups in future randomized controlled trials. The purpose of this review is to review and compare early neuroimaging findings that predict clinical outcome in acute basilar artery occlusion.